Integrating Ecological Principles for Addressing Plant Production Security and Move beyond the Dichotomy ‘Good or Bad’ for Nitrogen Inputs Choice - Maria Amélia Martins-Loução; Teresa Dias; Cristina Cruz (Agronomy, 2022)
Mankind’s strong dependence on nitrogen (N) began when we started farming and, ever since, we have depended on nitrogen in the soil for plant production. More than a century has passed since the discovery of N as an element until the advent of synthetic fertilizers. Today, after a century of Haber–Bosch innovation, many other endeavors and challenges can be launched to understand how the effects of N in the environment can be perceived as ‘good’ or ‘bad’. All this knowledge evolution was truly dependent on the scientific advances, both technological and methodological, and particularly on the approaches at the micro and macro level. As with nearly everything in our lives (e.g., events, people, food, decisions, world history), we tend to use the dichotomy ‘good or bad’ to categorize, and scientific advances are no exception. The integration of scientific and technological advances allows us to move beyond this simple dichotomy ‘good or bad’ and to make choices. Here, we review the main marks in understanding plant nutrition throughout time, with special emphasis on N, from the Greeks to the most recent trends in the 21st century. Since improving plant N use efficiency is a main avenue to meet several Sustainable Developmental Goals (e.g., SDG2 zero hunger, SDG12 responsible production and consumption, SDG15 life on land), the European Green Deal, and The Farm to Fork strategy, we propose that the ecological principles must be integrated in agro-ecosystem management. During the last 40 years, our research group has contributed to: (i) the clarification of the so-called dichotomy of choices when it comes to the environmental effects of N; and (ii) fetching natural solutions for N manmade problems. This was based on the knowledge that life is a continuous symbiotic interplay between mutualism and parasitism depending on environmental conditions and that there is a need for feeding people, assuring food quality and diminishing environmental impacts. We argue that, as a society, we have the scientific and technological means to learn from nature and to apply the ecological rules in agro-ecosystems. However, this is a choice we must make as individuals and as a society.